Photovoltaic encapsulant film comprising fumed alumina

By using curable compositions of materials such as polyolefins, a high volume resistivity crosslinked polymer composition is formed, which solves the problem of low volume resistivity of the existing PV sealant film, improves the resistance to potential-induced deterioration, and enhances the The power stability of the PV module.

CN114514276BActive Publication Date: 2025-02-25DOW GLOBAL TECHNOLOGIES LLC
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN201980100642.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2019-08-30
Publication Date
2025-02-25
Estimated Expiration
2039-08-30

AI Technical Summary

Technical Problem

The volume resistivity (VR) of existing PV sealant films is low, resulting in insufficient potential induced deterioration (PID) resistance performance, affecting the stability of the module's power.

Method used

A curable composition comprising polyolefin, pyrolytic alumina, organic peroxide, silane coupling agent and crosslinking additive is used to form a crosslinking polymer composition with a high volume resistivity through crosslinking reaction, using In preparation of PV sealant film.

Benefits of technology

The volume resistivity of the PV sealant film is significantly improved, and its resistance to PID is enhanced, thereby improving the power stability of the PV module.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003557668690000081
    Figure BDA0003557668690000081
  • Figure BDA0003557668690000281
    Figure BDA0003557668690000281
Patent Text Reader

Abstract

The present disclosure relates to a curable composition for a sealant film, the curable composition comprising: (A) a polyolefin; (B) a fumed alumina; (C) an organic peroxide; (D) a silane coupling agent; (E) a crosslinking aid; and, optionally, (F) an additive component comprising a UV stabilizer, wherein the volume resistivity of the polyolefin is less than 4.0E+15 ohm.cm. The present disclosure further relates to a sealant film made from such a curable composition and a PV module containing such a sealant film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to polyolefin-based photovoltaic (PV) encapsulant films having improved volume resistivity and PV modules containing such encapsulant films. Background Art

[0002] Ethylene vinyl acetate (EVA) is currently widely used as a sealant material for PV cells due to its transparency, flexibility and easy conversion into cross-linkable sheets. However, EVA has poor weather resistance and high polarity, resulting in low volume resistivity (VR). VR is important because it affects the potential induced degradation (PID) resistance performance. Sealed solar cells with low VR sealant materials may result in significant module power losses due to PID.

[0003] Polyolefin-based encapsulants, such as ethylene / α-olefin copolymers, have excellent transparency, adhesion, heat resistance, and can be easily converted into cross-linkable films. Although polyolefin-based encapsulants generally have improved VR compared to EVA, the VR range for such materials is wide, with VR greater than 10. 17 The best PID prevention performance is achieved with polyolefins having a VR of 0.1 ohm.cm. Polyolefins with lower VR will benefit from improvements in VR. Therefore, there is a need to improve the VR of PV encapsulant films containing low VR polyolefins. Summary of the invention

[0004] The present disclosure relates to a curable composition for a sealant film, the curable composition comprising: (A) a polyolefin; (B) a fumed alumina; (C) an organic peroxide; (D) a silane coupling agent; (E) a crosslinking aid; and, optionally, (F) an additive component comprising an antioxidant and / or a UV stabilizer, wherein the volume resistivity of the polyolefin is less than 4.0E+15 ohm.cm.

[0005] The present disclosure further relates to a sealant film comprising a cross-linked polymeric composition, which is the reaction product of a curable composition, the curable composition comprising: (A) a polyolefin; (B) fumed alumina; (C) an organic peroxide; (D) a silane coupling agent; (E) a cross-linking aid; and, optionally, (F) an additive component comprising an antioxidant and / or a UV stabilizer, wherein the volume resistivity of the polyolefin is less than 4.0E+15 ohm.cm.

[0006] The present disclosure further relates to a PV module comprising solar cells and at least one sealant film layer, wherein the sealant film layer comprises a cross-linked polymeric composition, which is the reaction product of a curable composition, wherein the curable composition comprises: (A) a polyolefin; (B) fumed alumina; (C) an organic peroxide; (D) a silane coupling agent; (E) a cross-linking aid; and, optionally, (F) an additive component comprising an antioxidant and / or a UV stabilizer, wherein the volume resistivity of the polyolefin is less than 4.0E+15 ohm.cm.

[0007] definition

[0008] All references herein to the Periodic Table of the Elements shall refer to the Periodic Table published and copyrighted by CRC Press, Inc. in 2003. Furthermore, any reference to one or more Groups shall be to the Group or Groups reflected in such Periodic Table using the IUPAC system for numbering the Groups.

[0009] For purposes of U.S. patent practice, the contents of any cited patent, patent application, or publication are incorporated by reference in their entirety (or their equivalent U.S. versions are incorporated by reference), particularly with respect to disclosure of definitions (to the extent not inconsistent with any definitions specifically provided in this disclosure) and common knowledge in the art.

[0010] The numerical ranges disclosed herein include all values ​​from the lower limit to the upper limit and include the lower limit and the upper limit. For ranges containing explicit values ​​(e.g., 1 or 2 or 3 to 5 or 6 or 7), any subranges between any two explicit values ​​are included (e.g., the above range 1-7 includes all subranges 1 to 2; 2 to 6; 5 to 7; 3 to 7; 5 to 6; etc.).

[0011] "Polymer" refers to a compound prepared by polymerizing monomers, whether of the same or different type. The generic term "polymer" thus embraces the term "homopolymer" to refer to polymers prepared from only one type of monomer, and the terms "interpolymer" or "copolymer" as defined herein. Trace amounts of impurities, such as catalyst residues, can be incorporated into and / or within the polymer.

[0012] "Polyolefin" is a polymer produced by polymerization of olefins as monomers, wherein olefin monomers are straight-chain, branched or cyclic compounds of carbon and hydrogen having at least one double bond. Polyolefins, which may be used interchangeably with "olefin-based polymers", contain more than 50% polymerized olefin monomers (by the total weight of the polyolefin olefins), and optionally, may contain one or more comonomers. Non-limiting examples of polyolefins include ethylene-based polymers and propylene-based polymers.

[0013] The term "interpolymer" refers to a polymer prepared by polymerizing at least two different types of monomers. This term includes both "copolymers," i.e., polymers prepared from two different types of monomers, and polymers prepared from more than two different types of monomers, such as terpolymers, tetrapolymers, etc. This term also encompasses all forms of interpolymers, such as random, block, homogeneous, heterogeneous, etc.

[0014] "Alpha-olefins" or "α-olefins" are hydrocarbon molecules that contain an olefinic unsaturation bond, the unsaturation bond being located between a first and a second carbon atom. For purposes of this disclosure, non-limiting examples of α-olefins include ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-dodecene, and mixtures of two or more of these monomers.

[0015] "Ethylene-based polymer" or "ethylene polymer" is a polymer that contains a majority amount (greater than 50 wt%) polymerized ethylene, based on the weight of the polymer, and optionally may further contain polymerized units of at least one comonomer.

[0016] "Ethylene-based interpolymers" are interpolymers that contain, in polymerized form, a majority amount (greater than 50 weight percent) of ethylene, based on the weight of the interpolymer, and further contain polymerized units of at least one comonomer. The ethylene-based interpolymers are either random interpolymers (i.e., contain a random distribution of its monomer components) or block interpolymers.

[0017] "Ethylene / α-olefin interpolymer" is an interpolymer containing a majority amount (greater than 50 weight percent) polymerized ethylene, based on the weight of the interpolymer, and further containing polymerized units of at least one α-olefin. The ethylene / α-olefin interpolymer can be a random interpolymer or a block interpolymer.

[0018] "Ethylene / α-olefin copolymers" are copolymers containing a major amount (greater than 50 wt%) of polymerized ethylene based on the weight of the copolymer and further containing polymerized units of an α-olefin. The ethylene / α-olefin copolymers may be random copolymers or block copolymers.

[0019] The term "olefin block copolymer" or "OBC" refers to an ethylene / α-olefin multi-block interpolymer and comprises ethylene and one or more copolymerizable α-olefin comonomers in polymerized form, characterized by multiple blocks or segments of two or more (preferably three or more) polymerized monomer units, said blocks or segments differing in chemical or physical properties. Specifically, the term "olefin block copolymer" refers to a polymer comprising two or more (preferably three or more) chemically distinct regions or segments (referred to as "blocks") joined in a linear manner rather than in a pendant or grafted manner, i.e., a polymer comprising chemically distinct units joined end-to-end (covalently bonded) with respect to polymerized functional groups. The blocks differ in the amount or type of comonomer incorporated therein, density, amount of crystallinity, type of crystallinity (e.g., polyethylene versus polypropylene), crystallite size attributable to polymers of such composition, type or degree of tacticity (isotactic or syndiotactic), regioregularity or regioirregularity, amount of branching (including long chain branching or hyperbranching), uniformity, and / or any other chemical or physical property. Block copolymers are characterized by unique distributions of both polymer polydispersity (PDI or Mw / Mn) and block length distribution, for example, based on the effect of using one or more shuttling agents in combination with a catalyst system. Non-limiting examples of the disclosed olefin block copolymers and methods for making the same are disclosed in U.S. Pat. Nos. 7,858,706 B2, 8,198,374 B2, 8,318,864 B2, 8,609,779 B2, 8,710,143 B2, 8,785,551 B2, and 9,243,090 B2, all of which are incorporated herein by reference in their entirety.

[0020] A "blend" or "polymer blend" is a composition of two or more polymers. Such blends may or may not be miscible. Such blends may or may not be phase separated. Such blends may or may not contain one or more domain configurations as determined by transmission electron spectroscopy, light scattering, x-ray scattering, and any other method known in the art.

[0021] A "composition" or "formulation" is a mixture or blend of two or more components. In the case of a mixture or blend of materials used to make an article, the composition includes all of the components in the mixture, such as polymers, catalysts, and any other additives or agents, such as curing catalysts, antioxidants, flame retardants, etc.

[0022] Whether specifically disclosed or not, the terms "comprising," "including," "having," and similar terms are not intended to exclude the presence of any additional components, steps, or procedures. Unless stated to the contrary, all methods claimed by using "comprising" may include one or more additional steps, equipment parts or components, and / or materials. In contrast, the term "consisting essentially of" excludes any other components, steps, or procedures from the scope of any subsequent enumeration, except those that are not essential for operability. The term "consisting of" excludes any components, steps, or procedures that are not specifically described or listed. Unless otherwise stated, the term "or" refers to the members listed individually and in any combination.

[0023] "Direct contact" is a configuration in which two components are in physical contact with one another with no intervening layers and / or no intervening materials between portions of the two components in contact.

[0024] The term "film", including when referring to a "film layer" in a thicker article, unless explicitly specified with a thickness, includes any thin, flat extruded or cast article of generally uniform and uniform thickness, typically 25 microns to 1.25 millimeters (mm) or more. In a film, a "layer" can be very thin, such as in the case of a nanolayer or microlayer. As used herein, the term "sheet", unless explicitly specified with a thickness, includes any thin, flat extruded or cast article of generally uniform and uniform thickness greater than a "film".

[0025] "Glass" means a hard, brittle, transparent solid, such as used in windows, bottles or goggles, including, but not limited to, pure silicon dioxide (SiO2), soda-lime glass, borosilicate glass, sugar glass, mica flakes (Muscovy-glass), photovoltaic glass or aluminum oxynitride.

[0026] Terms such as "photovoltaic cell", "PV cell" and the like refer to structures containing one or more photovoltaic effect materials of any of several inorganic or organic types. For example, commonly used photovoltaic effect materials include one or more of known photovoltaic effect materials, including but not limited to crystalline silicon, polycrystalline silicon, amorphous silicon, (di) copper indium gallium selenide (CIGS), copper indium selenide (CIS), cadmium telluride, gallium arsenide, dye-sensitized materials, and organic solar cell materials. PV cells are generally of laminated structure and have at least one photoreactive surface that converts incident light into electric current. Photovoltaic cells are well known to practitioners in the art and are generally packaged into photovoltaic modules to protect the cells and allow them to be used in their various application environments, generally in outdoor applications. Photovoltaic cells can be flexible or rigid in nature and include photovoltaic effect materials and any protective coating surface materials applied in their production as well as appropriate wiring and electronic drive circuit systems.

[0027] "Photovoltaic module," "PV module," and like terms refer to a structure that includes PV cells. A PV module may also include a cover sheet, a front sealant film, a rear sealant film, and a backsheet, wherein the PV cells are sandwiched between the front sealant film and the rear sealant film. An exemplary non-limiting PV module may include a top layer, a front sealant layer, at least one photovoltaic cell, a plurality of such cells typically arranged in a linear or planar pattern, a rear sealant layer, and a backsheet. The front sealant layer is in direct contact with both the photovoltaic cells and is also in direct contact with a portion of the rear sealant layer. The front sealant layer and the rear sealant layer completely surround or encapsulate the photovoltaic cells. The backsheet may be a single layer structure or a multilayer structure or glass (making glass / glass PV modules) that protects the back of the PV module.

[0028] Test Method

[0029] Each measurable property disclosed herein is measured according to the methods discussed below.

[0030] Density is measured according to ASTM D792 Method B. Results are expressed in grams (g) per cubic centimeter (g / cc or g / cm 3 ) in the form of records.

[0031] Flexural modulus (2% secant) is measured according to ASTM D790 and is reported in psi.

[0032] Initial Glass Adhesion: The laminated sample was cut into three 1" wide specimens (cutting the backsheet and film layers). The 180° peel test was used to measure the glass adhesion strength (maximum glass adhesion strength and average glass adhesion strength from 1" to 2" delamination). The test was performed on an Instron™ 5565 under controlled environmental conditions. At least three specimens were tested to obtain an average value. The results are reported in Newtons per centimeter (N / cm).

[0033] Average Transmittance: The transmittance of the compression molded films was determined using a LAMBDA 950 UV / Vis spectrophotometer (PerkinElmer) equipped with a 150 mm integrating sphere. At least three samples were tested and the average transmittance from 380 nm to 1100 nm was collected. The results are reported in percent (%).

[0034] Melt index (MI) measurements were performed according to ASTM D1238 at 190°C / 2.16 kilogram (kg) weight and are reported in grams eluted per 10 minutes (g / 10 min).

[0035] Melt Crystallization and Glass Transition: Differential Scanning Calorimetry (DSC) can be used to measure the melting, crystallization, and glass transition behavior of polymers over a wide range of temperatures. For example, a TA Instruments Q1000 DSC equipped with a refrigerated cooling system (RCS) and an autosampler is used to perform this analysis. During the test, a nitrogen purge gas flow rate of 50 ml / min was used. Each sample was melt pressed into a film at about 175°C; the molten sample was then air cooled to room temperature (about 25°C). 3-10 mg of a 6 mm diameter sample was extracted from the cooled polymer, weighed, placed in a light aluminum pan (approximately 50 mg), and crimped closed. Analysis was then performed to determine its thermal properties.

[0036] The thermal behavior of the sample is determined by ramping the sample temperature up and down to produce a heat flow versus temperature curve. First, the sample is quickly heated to 180°C and kept isothermal for 3 minutes to remove its thermal history. Next, the sample is cooled to -40°C at a cooling rate of 10°C / minute and kept isothermal at -40°C for 3 minutes. Then, the sample is heated to 180°C at a heating rate of 10°C / minute (this is the "second heating" ramp). Record the cooling and second heating curves. The cooling curve is analyzed by setting a baseline endpoint from the start of crystallization to -20°C. The heating curve is analyzed by setting a baseline endpoint from -20°C to the end of melting. The measured values ​​are the extrapolated starting point of the melting Tm and the extrapolated starting point of the crystallization Tc. The heat of fusion (H f ) (in Joules per gram) and calculated % crystallinity using the following equation:

[0037] Crystallinity % = ((H f ) / 292J / g)x 100

[0038] Report the heat of fusion (H) from the second heating curve. f ) and the peak melting temperature. The peak crystallization temperature is determined from the cooling curve.

[0039] The melting point Tm is determined from the DSC heating curve by first drawing a baseline between the start and end of the melting transition. A tangent line is then drawn to the data on the low temperature side of the melting peak. Where this tangent line intersects the baseline is the extrapolated onset of melting (Tm). This is as described in Bernhard Wunderlich, The Basis of Thermal Analysis, in Thermal Characterization of Polymeric Materials 92, 277-278 (Edith A. Turi, ed., 2nd ed., 1997).

[0040] The crystallization temperature Tc is determined from the DSC cooling curve as above, except that a tangent line is drawn on the high temperature side of the crystallization peak. Where this tangent line intersects the baseline is the extrapolated onset of crystallization (Tc).

[0041] The glass transition temperature, Tg, is determined from a DSC heating curve in which half of the sample has reached the liquid heat capacity, as described in Bernhard Wunderlich, Fundamentals of Thermal Analysis in Thermal Characterization of Polymeric Materials 92, 278-279 (Edith A. Turi, ed., 2nd ed., 1997). Base lines are drawn from below and above the glass transition region and extrapolated through the Tg region. The temperature at the midpoint between these base lines is the Tg.

[0042] Moving Die Rheometer (MDR): The MDR is loaded with approximately 4 grams of each cast film. The MDR is run at 150°C for 25 minutes. A time vs. torque curve is recorded for each sample at a given interval. The maximum torque applied by the MDR during the 25 minute test interval (MH) is recorded in deciNewton meters (dNm). The MH typically corresponds to the maximum torque applied at 25 minutes. The time required for the torque to reach x% of the MH (t x ) is recorded in minutes. x is a standardized measurement used to understand the curing kinetics of each resin. The time to reach 90% of MH (t 90 ).

[0043] Volume Resistivity: Volume resistivity was determined by the following method based on ASTM D257. Volume resistivity was determined using a Keithley 6517 B electrometer in combination with a Keithley 8009 test fixture. The Keithley 8009 test chamber was located in a forced air oven capable of operating at high temperatures (maximum temperature 80°C). The leakage current was recorded from the instrument by the software and the volume resistivity (VR) was calculated using the following equation:

[0044]

[0045] Where ρ is the volume resistivity in ohm.cm, V is the applied voltage in volts, and A is the electrode contact area in cm 2 , I is the leakage current recorded after 10 minutes of applied voltage in amperes, and t is the thickness of the sample. The thickness of the compression molded film was measured before testing. Five points of the film were measured to obtain the average thickness for calculation. The test was performed at room temperature at 1000 volts. Two compression molded films were tested, and the VR recorded is the average of the two tests. The results are reported in ohm-centimeters (ohm.cm). DETAILED DESCRIPTION

[0046] Polyolefins

[0047] The (A) polyolefin of the present disclosure is any olefin-based homopolymer (wherein the olefin is the only monomer) or olefin-based interpolymer where the olefin is the major monomer (that is, the olefin-based interpolymer contains greater than 50 wt% of units derived from the olefin). In these embodiments where the polyolefin is an interpolymer, the comonomers are different C 2-20 Straight chain, branched or cyclic alpha-olefins. For the purpose of this disclosure, ethylene is an alpha-olefin. C used as a comonomer 2-20 Non-limiting examples of α-olefins include ethylene, propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, and 1-octadecene.

[0048] In certain embodiments, the polyolefin is an ethylene-based polymer, which is an ethylene / α-olefin interpolymer, which can be a random or block interpolymer. In other embodiments, the polyolefin is an ethylene-based polymer, which is an ethylene / α-olefin copolymer, which can be a random or block copolymer. Non-limiting examples of ethylene / α-olefin copolymers include copolymers of ethylene and C3-C8 α-olefins or C4-C8 α-olefins, such as ethylene / propylene copolymers, ethylene / 1-butene copolymers, ethylene / 1-hexene copolymers, ethylene / 1-octene copolymers, and combinations thereof.

[0049] In certain embodiments, the polyolefin is an ethylene / alpha-olefin random copolymer. Examples of ethylene / alpha-olefin copolymers include ethylene / propylene random copolymers, ethylene / 1-butene random copolymers, ethylene / 1-hexene random copolymers, ethylene / 1-octene random copolymers, and combinations thereof. In certain embodiments, the polyolefin is an ethylene / alpha-olefin random copolymer, wherein the alpha-olefin is selected from 1-octene, 1-hexene, 1-butene, and propylene. In further embodiments, the polyolefin is an ethylene / 1-octene random copolymer.

[0050] In further embodiments, the polyolefin is an olefin block copolymer, and further is an ethylene / α-olefin multi-block interpolymer as defined herein.

[0051] In certain embodiments, the polyolefin is free of heteroatoms. As used herein, the term "heteroatom" is an atom other than carbon or hydrogen. The heteroatom can be a non-carbon atom of Groups IV, V, VI, and VII of the Periodic Table of Elements. Non-limiting examples of heteroatoms include: F, N, O, P, B, S, and Si.

[0052] In some embodiments, the volume resistivity of the polyolefin is greater than 1.0E+12ohm.cm to less than 4.0E+15ohm.cm, or greater than 5.0E+12ohm.cm to less than 4.0E+15ohm.cm, or greater than 1.0E+13ohm.cm to less than 4.0E+15ohm.cm, or greater than 5.0E+13ohm.cm to less than 4.0E+15ohm.cm, or greater than or equal to 1.0E+14ohm.cm to less than 4.0E+15ohm.cm, or greater than or equal to 5.0E+14ohm.cm to less than 4.0E+15ohm.cm, or greater than or equal to 5.0E+14ohm.cm to less than or equal to 3.5E+15ohm.cm, or greater than or equal to 7.0E+14ohm.cm to less than or equal to 3.0E+15ohm.cm.

[0053] In further embodiments, the volume resistivity of the polyolefin according to the methods disclosed herein or similar methods is 1.0E+12ohm.cm, or 5.0E+12ohm.cm, or 1.0E+13ohm.cm, or 5.0E+13ohm.cm, or 1.0E+14ohm.cm, or 5.0E+14ohm.cm, or 7.0E+14ohm.cm, or 9.0E+14ohm.cm, or 1.0E+15ohm.cm to 1.5E+15ohm.cm, or 2.0E+15ohm.cm, or 2.5E+15ohm.cm, or 3.0E+15ohm.cm, or 3.5E+15ohm.cm, or less than 4.0E+15ohm.cm.

[0054] In certain embodiments, the polyolefin has a density from 0.850 g / cc, or 0.855 g / cc, or 0.860 g / cc, or 0.865 g / cc, or 0.870 g / cc, or 0.875 g / cc to 0.880 g / cc, or 0.885 g / cc, or 0.890 g / cc, or 0.895 g / cc, or 0.900 g / cc, or 0.905 g / cc, or 0.910 g / cc, or 0.915 g / cc, or 0.920 g / cc, as measured according to ASTM D792 Method B. For example, in certain embodiments, the polyolefin has a density of 0.850 g / cc to 0.920 g / cc, or 0.855 g / cc to 0.910 g / cc, or 0.860 g / cc to 0.900 g / cc, or 0.860 g / cc to 0.895 g / cc, or 0.860 g / cc to 0.890 g / cc, or 0.865 g / cc to 0.885 g / cc, or 0.865 g / cc to 0.880 g / cc, as measured according to ASTM D792 Method B.

[0055] In certain embodiments, the polyolefin has a melt index (MI) of 0.1 g / 10 min, or 0.5 g / 10 min, or 1 g / 10 min, or 5 g / 10 min, or 10 g / 10 min, or 12 g / 10 min to 18 g / 10 min, or 20 g / 10 min, or 25 g / 10 min, or 30 g / 10 min, or 50 g / 10 min, or 75 g / 10 min, or 100 g / 10 min, as measured at 190°C / 2.16 kg according to ASTM D1238. For example, in certain embodiments, the polyolefin has a melt index (MI) of 0.1 g / 10 min to 100 g / 10 min, or 0.5 g / 10 min to 100 g / 10 min, or 1 g / 10 min to 100 g / 10 min, or 1 g / 10 min to 75 g / 10 min, or 1 g / 10 min to 50 g / 10 min, or 1 g / 10 min to 30 g / 10 min, or 5 g / 10 min to 30 g / 10 min, or 5 g / 10 min to 20 g / 10 min, as measured according to ASTM D1238 at 190° C. and 2.16 kg.

[0056] In certain embodiments, the polyolefin has a melting point (Tm) of 55°C, or 60°C, or 75°C, or 90°C, or 95°C, or 100°C to 105°C, or 110°C, as measured using DSC.

[0057] In a certain embodiment, the olefin-based polymer has a glass transition temperature, Tg, as measured using DSC, of ​​-30°C, or -35°C to -40°C, or -45°C, or -50°C, or -60°C.

[0058] In an embodiment, the olefin-based polymer has a flexural modulus (2% secant) of greater than or equal to 500 psi, or greater than or equal to 750 psi, or greater than or equal to 1000 psi to 2000 psi, or 3000 psi, or 3500 psi, or 4000 psi, or less than 6000 psi, as measured according to ASTM D790.

[0059] Suitable polyolefins according to the present disclosure include, but are not limited to, polyolefins that can be used as ENGAGE TM Polyolefin elastomers and INFUSE TM Olefin block copolymers are available from The Dow Chemical Company as Exact TM Plastomers are those available from ExxonMobil Chemical Company and those available as LUCENE TMPolyolefins were those purchased from LG Chemical.

[0060] Blends of any of the above polyolefins may also be used, provided that the volume resistivity of the blend is less than 4.0E+15 ohm.cm. The polyolefin or blend thereof may be blended or diluted with one or more other polymers until the polyolefin and other polymers (i) are miscible with each other, (ii) the other polymers have little, if any, effect on the desired properties of the polyolefin (i.e., optics and low modulus), and (iii) the polyolefin comprises greater than 50 wt%, or 60 wt%, or 70 wt%, or 75 wt%, or 80 wt% to 90 wt%, or 95 wt%, or 98 wt%, or 99 wt%, or less than 100 wt% of the blend, based on the total weight of the blend.

[0061] The polyolefins of the present disclosure may be any combination of the embodiments disclosed herein.

[0062] Fumed Alumina

[0063] Fumed alumina (alumina) is a type of synthetic alumina. As a synthetic alumina, the fumed alumina disclosed herein has high chemical purity and high specific surface area. In another embodiment, the fumed alumina can be prepared by a flame hydrolysis process known in the art, such as similar to The flame hydrolysis process used to make fumed alumina can be controlled by varying the concentrations of the reactants, the flame temperature and certain residence times. This will affect the particle size, particle size distribution, specific surface area and surface characteristics of the fumed alumina product. In other words, different fumed alumina products can be made depending on how the process is controlled.

[0064] Unless specially treated, fumed alumina particles prepared by the flame hydrolysis process are inherently hydrophilic. To form hydrophobic fumed alumina silica particles, the hydrophilic fumed alumina particles are chemically post-treated with a hydrophobizing agent. Suitable hydrophobizing agents include, but are not limited to, organosilane compounds such as alkoxysilanes, silazanes, and siloxanes. As used herein, the term "hydrophobically treated fumed alumina" is fumed alumina in particle form in which the hydrophobizing agent is bonded to the particle surface via one or more oxygen covalent bonds.

[0065] In certain embodiments, the fumed alumina of the present disclosure is a hydrophilic fumed alumina. In other embodiments, the fumed alumina of the present disclosure is a hydrophobic treated fumed alumina. The fumed alumina of the present disclosure may be a thermodynamically stable alpha form or a metastable gamma form, including gamma, delta, and theta forms.

[0066] In certain embodiments, the fumed alumina has a specific surface area (BET) greater than 50 m2 / g to less than 200m 2 In certain embodiments, the specific surface area (BET) of the fumed alumina is 55 m 2 / g to 150m 2 / g, or 60m 2 / g to 140m 2 / g, or 65m 2 / g to 130m 2 In another embodiment, the specific surface area (BET) of the fumed alumina is 55 m 2 / g, or 60m 2 / g, or 65m 2 / g, or 70m 2 / g, or 75m 2 / g, or 80m 2 / g, or 85m 2 / g to 95m 2 / g, or 100m 2 / g, or 105m 2 / g, or 110m 2 / g, or 115m 2 / g, or 120m 2 / g, or 130m 2 / g, or 140m 2 / g, or 150m 2 / g, or less than 200m 2 / g.

[0067] Non-limiting examples of hydrophilic fumed aluminas are Alu 65 and Alu 130 are available from Evonik Industries. Non-limiting examples of hydrophobically treated fumed aluminas are available as Alu C those purchased from Evonik Industries.

[0068] The fumed alumina of the present disclosure may be a blend of hydrophilic fumed alumina and hydrophobically treated fumed alumina, or may be a blend of more hydrophilic fumed alumina than hydrophilic fumed alumina.

[0069] The fumed alumina of the present disclosure may be any combination of the embodiments disclosed herein.

[0070] Organic peroxide

[0071] An organic peroxide is a molecule containing carbon atoms, hydrogen atoms and two or more oxygen atoms and having at least one -OO- group, such that when more than one -OO- group is present, each -OO- group is indirectly bonded to another -OO- group or a collection of such molecules via one or more carbon atoms. An organic peroxide may be of formula R O -OOR O A monoperoxide, where each R O Independently (C1-C 20 )alkyl or (C6-C 20 ) aryl. Each (C1-C 20 ) alkyl is independently unsubstituted or substituted with 1 or 2 (C6-C 12 ) aryl substituted. Each (C6-C 20 ) aryl is unsubstituted or substituted with 1 to 4 (C1-C 10 Alternatively, the organic peroxide may be of formula R O -OOROOR O A diperoxide, wherein R is a divalent hydrocarbon group, such as (C2-C 10 ) alkylene, (C3-C 10 ) cycloalkylene or phenylene, and each R O As defined above. Suitable organic peroxides include, but are not limited to, alkyl peroxides, aryl peroxides, peroxyesters, peroxycarbonates, diacyl peroxides, peroxyketals, cyclic peroxides, dialkyl peroxides, peroxyesters, peroxydicarbonates, or combinations of two or more thereof.

[0072] Examples of suitable organic peroxides include, but are not limited to, diisopropyl peroxide; dodecyl peroxide; benzoyl peroxide; tert-butyl perbenzoate; di(tert-butyl peroxide); cumene hydroperoxide; 2,5-dimethyl-2,5-di(tert-butyl-peroxy)hexyne-3; 2,-5-dimethyl-2,5-di(tert-butyl-peroxy)hexane; tert-butyl hydroperoxide; isopropyl percarbonate; α,α'-bis(tert-butylperoxy)diisopropylbenzene, tert-butylperoxy-2-ethylhexyl-monocarbonate; 1,1-bis(tert-butylperoxy)-3,5,5-trimethylcyclohexane; 2,5-dimethyl-2,5-dihydroxyperoxide; tert-butyl peroxide cumyl; α,α'-bis(tert-butylperoxy)-p-diisopropylbenzene; bis(1,1-dimethylethyl)peroxide; bis(1,1-dimethylpropyl)peroxide;

[0073] 2,5-Dimethyl-2,5-bis(1,1-dimethylethylperoxy)hexane; 2,5-Dimethyl-2,5-bis(1,1-dimethylethylperoxy)hexyne; 4,4-bis(1,1-dimethylethylperoxy)pentanoic acid; butyl ester; 1,1-bis(1,1-dimethylethylperoxy)-3,3,5-trimethylcyclohexane; benzoyl peroxide; tert-butyl peroxybenzoate; di-tert-amyl peroxide ("DTAP"); bis(alpha-tert-butylperoxyisopropyl)benzene

[0074] ("BIPB"); isopropylcumyl tert-butyl peroxide; tert-butyl cumyl peroxide; di-tert-butyl peroxide; 2,5-bis(tert-butylperoxy)-2,5-dimethylhexane; 2,5-bis(tert-butylperoxy)-2,5-dimethylhexyne-3,1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane; isopropylcumyl cumyl peroxide; butyl 4,4-di(tert-butylperoxy)valerate; di(isopropylcumyl) peroxide; and combinations thereof.

[0075] Non-limiting examples of suitable commercially available organic peroxides include and from ARKEMA TBEC.

[0076] Silane coupling agent

[0077] In some embodiments, the silane coupling agent contains at least one alkoxy group. Non-limiting examples of suitable silane coupling agents include γ-chloropropyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyl-tri-(β-methoxy)silane, allyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, β-(3,4-ethoxy-cyclohexyl)ethyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, and 3-(trimethoxysilyl)propylmethacrylate, vinyltriacetoxysilane, γ-(meth)acryloxy, propyltrimethoxysilane, and combinations thereof.

[0078] In some embodiments, the silane coupling agent is vinyltrimethoxysilane (VTMS) or 3-(trimethoxysilyl)propyl methacrylate (VMMS) or allyltrimethoxysilane.

[0079] Crosslinking aid

[0080] The crosslinking auxiliary agent may be any one or a mixture of the following auxiliary agents including, but not limited to, esters, ethers, ketones, cyanurates, isocyanurates, phosphates, orthoformates, aliphatic or aromatic ethers containing at least 2 and preferably 3 unsaturated groups, such as allyl, vinyl or acrylate. The number of carbon atoms in the auxiliary agent may be in the range of 9 to 40 or more, and preferably 9 to 20.

[0081] Specific examples of the auxiliary agent include, but are not limited to, triallyl cyanurate (TAC); triallyl-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, also known as triallyl isocyanurate (TAIC); hexaallyl melamine; triallyl phosphate (TAP); triallyl orthoformate; tetraallyloxyethane; triallylbenzene-1,3,5-tricarboxylate; diallyl phthalate; zinc dimethacrylate; ethoxylated bisphenol A dimethacrylate; methacrylate sealants with an average chain length of C14 or C15 Terminal monomer; pentaerythritol tetraacrylate; dipentaerythritol pentaacrylate; pentaerythritol triacrylate; dimethylolpropane tetraacrylate; ethoxylated trimethylolpropane triacrylate; trimethylolpropane triacrylate; 2,4,6-triallyl-1,3,5-trione; 2,4-diphenyl-4-methyl-1-pentene; triallyl trimellitate (TATM); 3,9-divinyl-2,4,8,10-tetraoxaspiro[5.5]undecane (DVS); α-methylstyrene dimer (AMSD); and combinations thereof.

[0082] In certain embodiments, the cross-linking aid may be selected from the group consisting of TAIC, TAC, TAP, vinyl cyclic siloxane, and combinations thereof.

[0083] Additive components

[0084] The curable compositions of the present disclosure may contain one or more additives. Non-limiting examples of suitable additives include other polymers, metal oxides, antioxidants, fillers, UV stabilizers, flame retardants, plasticizers or oils, colorants or pigments, tackifiers, reinforcing agents, fatty acids and their salts, anti-ignition additives, scorch inhibitors, stabilizers, foaming agents, lubricants, processing aids, extrusion aids, nucleation agents, scavengers, waxes, curing additives, accelerators, and combinations thereof.

[0085] In certain embodiments, the curable composition of the present disclosure includes an additive component, and the additive component includes an antioxidant and / or a UV stabilizer. Therefore, the additive component may include a UV stabilizer. Alternatively, the additive component may include an antioxidant. In addition, the additive component may include an antioxidant and a UV stabilizer.

[0086] Non-limiting examples of suitable UV stabilizers include hindered phenols, phosphites, hindered amine light stabilizers (HALS), UV absorbers, hindered benzoates, and combinations of these. Suitable UV stabilizers include, but are not limited to, T770 available from TCI; UV 531 available from TCI; Cynergy A400, A430, and R350; Cyasorb UV-3529; Cyasorb UV-3346; Cyasorb UV-3583; Hostavin N30; Univil 4050; Univin 5050; Chimassorb UV-119; Chimassorb 944 LD; Tinuvin 622 LD; benzophenones, benzotriazoles, triazines, and combinations of these, such as Tinuvin 328 or Cyasorb UV-1164; and the like.

[0087] Suitable antioxidants include, but are not limited to, those selected from the group consisting of: Cyanox 2777; Irganox 1010; Irganox 1076; Irganox B215; Irganox B225; PEPQ; Weston 399; TNPP; Irgafos 168; and Devoerphos 9228.

[0088] Curable composition

[0089] The present disclosure relates to a curable composition for a sealant film, the curable composition comprising: (A) a polyolefin; (B) a fumed alumina; (C) an organic peroxide; (D) a silane coupling agent; (E) a crosslinking aid; and, optionally, (F) an additive component comprising an antioxidant and / or a UV stabilizer, wherein the volume resistivity of the polyolefin is less than 4.0E+15 ohm.cm.

[0090] The (A) polyolefin having a volume resistivity of less than 4.0E+15 ohm.cm may be present in the curable composition in an amount of 80 wt % to 99 wt %, or 85 wt % to 99 wt %, or 90 wt % to 99 wt %, or 95 wt % to 99 wt %, based on the total weight of the curable composition.

[0091] (B) fumed alumina may be present in the curable composition in an amount of 0.01 wt % to 5 wt %, or 0.05 to 2 wt %, or 0.1 wt % to 1 wt %, or 0.25 wt % to 1 wt %, based on the total weight of the curable composition.

[0092] The (C) organic peroxide may be present in the curable composition in an amount of 0.1 wt % to 5 wt %, or 0.1 wt % to 3 wt %, or 0.5 wt % to 2 wt %, based on the total weight of the curable composition.

[0093] The (D) silane coupling agent may be present in the curable composition in an amount of 0.01 wt % to 2 wt %, or 0.05 wt % to 1 wt %, or 0.1 wt % to 0.5 wt %, based on the total weight of the curable composition.

[0094] The (E) crosslinking aid may be present in the curable composition in an amount of 0.01 wt % to 5 wt %, or 0.1 wt % to 3 wt %, or 0.2 wt % to 1 wt %, based on the total weight of the curable composition.

[0095] The (F) additive component comprising an antioxidant and / or a UV stabilizer may be present in the curable composition in an amount of 0 wt % to 5 wt %, or 0 wt % to 3 wt %, or 0 wt % to 1 wt %, or 0.01 wt % to 1 wt %, based on the total weight of the curable composition.

[0096] In certain embodiments, the curable composition of the present invention may further include one or more polymers other than (A) polyolefin. That is, (A) polyolefin can be blended with one or more polymers. Therefore, the curable composition of the present invention (and the cross-linked polymer composition of the reaction product comprising the curable composition) may further include one or more polymers, including but not limited to unsaturated polyolefins (another EPDM, polybutadiene, etc.), saturated polyolefins (PE, PP, ethylene / α-olefin interpolymers, propylene / α-olefin interpolymers, olefin block copolymers, etc.), other elastomers (SBC, PVC, EVA, etc.) and other engineering thermoplastics (styrene, polyamide, polyester, etc.).

[0097] In certain embodiments, the polyolefin is not blended with other polymers. In certain embodiments, the curable composition is absent (or does not include) any polymer other than (A) the polyolefin.

[0098] The curable composition of the present disclosure can be cured to form a crosslinked polymeric composition. The crosslinked polymeric composition is the reaction product of the curable composition resulting from curing.

[0099] In some embodiments, according to the methods disclosed herein or similar methods, the volume resistivity of the cross-linked polymeric composition is greater than 1.0E+15ohm.cm, or greater than 5.0E+15ohm.cm, or greater than or equal to 9.0E+15ohm.cm, or greater than or equal to 1.0E+16ohm.cm, or greater than or equal to 2.0E+16ohm.cm, or greater than or equal to 5.0E+16ohm.cm, or greater than or equal to 8.0E+16ohm.cm, or greater than or equal to 1.0E+17ohm.cm, or greater than or equal to 5.0E+17ohm.cm, or greater than or equal to 1.0E+18ohm.cm, or greater than or equal to 1.0E+19ohm.cm.

[0100] In other embodiments, according to the methods disclosed herein or similar methods, the volume resistivity of the cross-linked polymeric composition is from 1.0E+15ohm.cm or 5.0E+15ohm.cm or 9.0E+15ohm.com to 1.0E+16ohm.cm, or 2.0E+16ohm.cm, or 5.0E+16ohm.cm, or 8.0E+16ohm.cm, or 9.0E+16ohm.cm, or 1.0E+17ohm.cm, 5.0E+17ohm.cm, or 1.0E+18ohm.cm, or 1.0E+19ohm.cm. For example, in certain embodiments, the volume resistivity of the cross-linked polymeric composition is greater than 1.0E+15ohm.cm to 1.0E+19ohm.cm, or greater than 1.0E+15ohm.cm to 1.0E+18ohm.cm, or greater than 1.0E+15ohm.cm to 5.0E+17ohm.cm, or greater than 1.0E+15ohm.cm to 1.0E+17ohm.cm, or greater than 5.0E+15ohm.cm to 1.0E+17, or greater than 9.0E+15ohm.cm to 9.0E+16ohm.cm.

[0101] Each of the curable composition and the cross-linked polymeric composition can have any combination of the embodiments described herein.

[0102] Sealant film or film layer

[0103] The present disclosure provides a sealant film or film layer that can be incorporated into an electronic device such as a PV module. The sealant film or film layer is made of a curable composition or a cross-linked polymeric composition described herein. In certain embodiments, the present disclosure relates to a sealant film or film layer, which comprises a cross-linked polymeric composition as a reaction product of a curable composition, wherein the curable composition comprises: (A) a polyolefin; (B) fumed alumina; (C) an organic peroxide; (D) a silane coupling agent; (E) a cross-linking aid; and, optionally (F) an additive component comprising an antioxidant and / or a UV stabilizer, wherein the volume resistivity of the polyolefin is less than 4.0E+15 ohm.cm. In certain embodiments, the sealant film or film layer is a cross-linked polymeric composition.

[0104] In further embodiments, the present disclosure relates to a sealant film or film layer comprising a crosslinked polymeric composition as a reaction product of a curable composition comprising: (A) 80 wt% to 99 wt%, or 85 wt% to 99 wt%, or 90 wt% to 99 wt%, or 95 wt% to 99 wt% of a polyolefin having a volume resistivity of less than 4.0E+15 ohm.cm, based on the total weight of the curable composition; (B) 0.01 wt% to 5 wt%, or 0.05 to 2 wt%, or 0.1 wt% to 1 wt%, or 0.25 wt% to 1 wt% of fumed alumina, based on the total weight of the curable composition; (C) 0.1 wt% to 5 wt%, or 0.05 to 2 wt%, or 0.1 wt% to 1 wt%, or 0.25 wt% to 1 wt% of a polyolefin having a volume resistivity of less than 4.0E+15 ohm.cm, based on the total weight of the curable composition; (D) 0.01 wt % to 2 wt %, or 0.05 wt % to 1 wt %, or 0.1 wt % to 0.5 wt % of a silane coupling agent, based on the total weight of the curable composition; (E) 0.01 wt % to 5 wt %, or 0.1 wt % to 3 wt %, or 0.2 wt % to 1 wt % of a crosslinking aid, based on the total weight of the curable composition; and (F) 0 wt % to 5 wt %, or 0 wt % to 3 wt %, or 0 wt % to 1 wt %, or 0.01 wt % to 1 wt % of an additive component comprising an antioxidant and / or a UV stabilizer, based on the total weight of the curable composition.

[0105] The sealant film or film layer can be formed by any means known in the art. In certain embodiments, the sealant film or film layer is prepared by extruding some or all components of the curable composition via various types of mixers or extruders (such as single screw or twin screw types), and then solidifying or crosslinking during molding and / or lamination. A typical extruder has a hopper at its upstream end and a mold at its downstream end. The components of the curable composition can be fed into the hopper, and then melted and extruded at a temperature lower than 120°C to not cause solidification or crosslinking. In certain embodiments, extrusion can be carried out at a rotor speed of 20rpm to 40rpm at a temperature of 85°C to 115°C.

[0106] Components (A) to (F) of the curable composition can be added to or combined with each other in any order before curing or crosslinking. For example, components (B) to (F) can be gradually added to (A) polyolefin in an extruder. In certain embodiments, (A) polyolefin can be soaked with components (C) to (E) before extrusion, and other components can be added during extrusion. In other embodiments, (A) polyolefin can be mixed or extruded with components (B) and (F), and then soaked with components (C) to (E).

[0107] It is desirable to avoid or limit the curing or crosslinking of the curable composition until a step after extrusion. Premature curing or crosslinking can result in reduced glass adhesion of the sealant film or film layer. Therefore, in certain embodiments, curing or crosslinking of the curable composition occurs after extrusion and during molding and / or lamination at elevated temperatures (e.g., greater than 120°C to 160°C). In other words, the sealant film remains active until molding and / or lamination, at which time curing or crosslinking is initiated to produce a sealant film or film layer comprising a crosslinked polymeric composition, the crosslinked polymeric composition being the reaction product of a curable composition comprising: (A) a polyolefin having a volume resistivity of less than 4.0E+15ohm.cm; (B) fumed alumina; (C) an organic peroxide; (D) a silane coupling agent; (E) a crosslinking aid; and, optionally (F) an additive component comprising an antioxidant and / or a UV stabilizer.

[0108] The sealant film or film layer can have any thickness suitable for inclusion in an electronic device such as a PV module. In certain embodiments, the sealant film or film layer has a thickness of 100 μm, or 150 μm, or 200 μm, or 250 μm, or 300 μm, or 350 μm, or 400 μm to 450 μm, or 500 μm, or 550 μm, or 600 μm, or 650 μm, or 700 μm, or 800 μm.

[0109] In some embodiments, according to the methods disclosed herein or similar methods, the volume resistivity of the sealant film or film layer of the present disclosure is greater than 1.0E+15ohm.cm, or greater than 5.0E+15ohm.cm, or greater than or equal to 9.0E+15ohm.cm, or greater than or equal to 1.0E+16ohm.cm, or greater than or equal to 2.0E+16ohm.cm, or greater than or equal to 5.0E+16ohm.cm, or greater than or equal to 8.0E+16ohm.cm, or greater than or equal to 1.0E+17ohm.cm, or greater than or equal to 5.0E+17ohm.cm, or greater than or equal to 1.0E+18ohm.cm, or greater than or equal to 1.0E+19ohm.cm.

[0110] In other embodiments, according to the methods disclosed herein or similar methods, the volume resistivity of the sealant film or film layer of the present disclosure is 1.0E+15ohm.cm, or 5.0E+15ohm.cm, or 9.0E+15ohm.com to 1.0E+16ohm.cm, or 2.0E+16ohm.cm, or 5.0E+16ohm.cm, or 8.0E+16ohm.cm, or 9.0E+16ohm.cm, or 1.0E+17ohm.cm, 5.0E+17ohm.cm, or 1.0E+18ohm.cm, or 1.0E+19ohm.cm. For example, the volume resistivity of the sealant film or film layer is greater than 1.0E+15ohm.cm to 1.0E+19ohm.cm, or greater than 1.0E+15ohm.cm to 1.0E+18ohm.cm, or greater than 1.0E+15ohm.cm to 5.0E+17ohm.cm, or greater than 1.0E+15ohm.cm to 1.0E+17ohm.cm, or greater than 5.0E+15ohm.cm to 1.0E+17, or greater than 9.0E+15ohm.cm to 9.0E+16ohm.cm.

[0111] In certain embodiments, the sealant film or film layer of the present disclosure has a maximum torque (MH) greater than or equal to 2.0 dNm, or greater than or equal to 2.5 dNm, or greater than or equal to 3.0 dNm, or greater than or equal to 3.5 dNm, or greater than or equal to 3.6 dNm, or greater than or equal to 3.7 dNm.

[0112] In further embodiments, the sealant film or film layer has a t90 of less than 15 minutes, or less than 13 minutes, or less than 11 minutes, or less than 10.9 minutes, or less than or equal to 10.8 minutes, or less than or equal to 10.7 minutes.

[0113] In some embodiments, the sealant film or film layer has an initial glass adhesion greater than 100 N / cm, or greater than 110 N / cm, or greater than 120 N / cm, or greater than 130 N / cm, or greater than 140 N / cm, or greater than 145 N / cm, or greater than or equal to 146 N / cm, or greater than or equal to 149 N / cm, or greater than or equal to 150 N / cm. In certain embodiments, according to the methods disclosed herein or similar methods, the sealant film or film layer has an initial glass adhesion of greater than 100 N / cm to 200 N / cm, or greater than 100 N / cm to 180 N / cm, or greater than 100 N / cm to 160 N / cm, or greater than 120 N / cm to 160 N / cm, or greater than 130 N / cm to 150 N / cm.

[0114] In certain embodiments, according to the methods disclosed herein or similar methods, the average transmittance of the sealant film or film layer is greater than or equal to 88%, or greater than or equal to 88.5%, or greater than or equal to 89%, or greater than or equal to 89.5%, or greater than or equal to 90%.

[0115] The sealant film or film layer of the present disclosure may be any combination of the embodiments disclosed herein.

[0116] Electronic Devices

[0117] The sealant films of the present disclosure can be incorporated into the construction of electronic devices such as PV modules. The sealant film can be used as one or more layers of a PV module. The sealant film can be applied to one or both skins of an electronic device, for example as a front sealant film or a rear sealant film, or as both a front sealant film and a rear sealant film, for example where the electronic device is completely encapsulated within the material.

[0118] A "photovoltaic module" or "PV module" is a laminate structure that may include, but is not limited to, the following layer components:

[0119] 1. Light receiving and transmitting layer;

[0120] 2. Front sealant film layer (transparent);

[0121] 3. One or more photovoltaic cells;

[0122] 4. A rear sealant film layer; and

[0123] 5. Back panel.

[0124] In an embodiment, the light receiving and transmitting layer is glass, acrylic resin, polycarbonate, polyester or fluorine-containing resin. In an embodiment, the light receiving and transmitting layer is glass.

[0125] The number of photovoltaic cells in a given photovoltaic module will vary depending on the nature and use of the electronic device utilizing the photovoltaic module.In an embodiment, at least one photovoltaic cell is in direct contact with the front and rear encapsulant film layers.

[0126] In an embodiment, the backplane is a polymer backplane or a glass backplane.

[0127] The layers (1) to (5) of the PV module having the above-mentioned laminated structure are bonded by lamination. By lamination, the top sheet is in direct contact with the front sealant film layer, and the back sheet is in direct contact with the rear sealant film layer. The photovoltaic cell is fixed between the front sealant film layer and the rear sealant film layer and is in direct contact with them. Therefore, parts of the front sealant film and the rear sealant film are in direct contact with each other.

[0128] In an embodiment, the present disclosure provides a PV module. The PV module includes a sealant film layer of the present disclosure. The film layer of the present disclosure can be a front sealant film layer, a rear sealant film layer, a back sheet film layer, and combinations thereof. In other embodiments, the film layer can be the entire film, or one or more discrete sub-layers of the film.

[0129] In an embodiment, the front sealant film layer and the rear sealant film layer are both film layers as disclosed herein. Each of the front sealant film layer and the rear sealant film layer directly contacts the photovoltaic cell. A portion of the front sealant film layer also directly contacts a portion of the rear sealant film layer. The front sealant film layer and the rear sealant film layer can be as previously described.

[0130] In an embodiment, a film layer comprising a composition of the present disclosure is applied to an electronic device by one or more lamination techniques. By lamination, a cover sheet is in direct contact with a first surface of the sealant film layer, and the electronic device is in direct contact with a second surface of the sealant film layer. In another embodiment, the cover sheet is in direct contact with a first surface of the front sealant film layer, a back sheet is in direct contact with a second surface of the rear sealant film layer, and the electronic device is fixed between and in direct contact with the second surface of the front sealant film layer and the first surface of the rear sealant film layer.

[0131] In embodiments, the lamination temperature is sufficient to activate the organic peroxide and crosslink the curable composition, that is, as disclosed herein, the curable composition comprising (A) a polyolefin having a volume resistivity of less than 4.0E+15 ohm.cm, (B) fumed alumina, (C) an organic peroxide, (D) a silane coupling agent, (E) a crosslinking aid, and optionally (F) an additive component comprising an antioxidant and / or a UV stabilizer, remains reactive until lamination when crosslinking occurs. After lamination, a crosslinked polymeric composition is formed as a reaction product of a curable composition comprising (A) a polyolefin having a volume resistivity of less than 4.0E+15 ohm.cm, (B) fumed alumina, (C) an organic peroxide, (D) a silane coupling agent, (E) a crosslinking aid, and optionally (F) an additive component comprising an antioxidant and / or a UV stabilizer.

[0132] In an embodiment, the lamination temperature for producing electronic devices is 130° C., or 135° C., or 140° C., or 145° C. to 150° C., or 155° C., or 160° C. In an embodiment, the lamination time is from 8 minutes, or 10 minutes, or 12 minutes, or 15 minutes to 18 minutes, or 20 minutes, or 22 minutes, or 25 minutes.

[0133] Specific embodiments of the present disclosure include but are not limited to the following:

[0134] 1. A curable composition for a sealant film, the curable composition comprising: (A) a polyolefin; (B) fumed alumina; (C) an organic peroxide; (D) a silane coupling agent; (E) a crosslinking aid; and, optionally, (F) an additive component comprising an antioxidant and / or a UV stabilizer, wherein the volume resistivity of the polyolefin is less than 4.0E+15 ohm.cm.

[0135] 2. The curable composition of embodiment 1, wherein the curable composition comprises:

[0136] (A) 80 wt% to 99 wt%, or 85 wt% to 99 wt%, or 90 wt% to 99 wt%, or 95 wt% to 99 wt% of a polyolefin, based on the total weight of the curable composition;

[0137] (B) 0.01 wt % to 5 wt %, or 0.05 to 2 wt %, or 0.1 wt % to 1 wt %, or 0.25 wt % to 1 wt % of fumed alumina, based on the total weight of the curable composition;

[0138] (C) 0.1 wt % to 5 wt %, or 0.1 wt % to 3 wt %, or 0.5 wt % to 2 wt % of an organic peroxide, based on the total weight of the curable composition;

[0139] (D) 0.01 wt % to 2 wt %, or 0.05 wt % to 1 wt %, or 0.1 wt % to 0.5 wt % of a silane coupling agent, based on the total weight of the curable composition;

[0140] (E) 0.01 wt % to 5 wt %, or 0.1 wt % to 3 wt %, or 0.2 wt % to 1 wt %, based on the total weight of the curable composition; and

[0141] (F) 0 wt % to 5 wt %, or 0 wt % to 3 wt %, or 0 wt % to 1 wt %, or 0.01 wt % to 1 wt % of a UV stabilizer, based on the total weight of the curable composition.

[0142] 3. The curable composition of embodiment 1 or 2, wherein the volume resistivity of the polyolefin is greater than 1.0E+12 ohm.cm to less than 4.0E+15 ohm.cm, or greater than 5.0E+12 ohm.cm to less than 4.0E+15 ohm.cm, or greater than 1.0E+13 ohm.cm to less than 4.0E+15 ohm.cm, or greater than 5.0E+13 ohm.cm to less than 4.0E+15 ohm.cm, or greater than or equal to 1.0E+14ohm.cm to less than 4.0E+15ohm.cm, or greater than or equal to 5.0E+14ohm.cm to less than 4.0E+15ohm.cm, or greater than or equal to 5.0E+14ohm.cm to less than or equal to 3.5E+15ohm.cm, or greater than or equal to 7.0E+14ohm.cm to less than or equal to 3.0E+15ohm.cm.

[0143] 4. The curable composition of any preceding embodiment, wherein the polyolefin has a density of 0.850 g / cc to 0.920 g / cc, or 0.855 g / cc to 0.910 g / cc, or 0.860 g / cc to 0.900 g / cc, or 0.860 g / cc to 0.895 g / cc, or 0.860 g / cc to 0.890 g / cc, or 0.865 g / cc to 0.885 g / cc, or 0.865 g / cc to 0.880 g / cc, as measured according to ASTM D792, Method B.

[0144] 5. The curable composition of any preceding embodiment, wherein the polyolefin has a melt index of 0.1 to 100 g / 10 min, or 0.5 to 100 g / 10 min, or 1 to 100 g / 10 min, or 1 to 100 g / 10 min, or 1 to 75 g / 10 min, or 1 to 50 g / 10 min, or 1 to 30 g / 10 min, or 5 to 30 g / 10 min, or 5 to 20 g / 10 min, as measured according to ASTM D1238 at 190°C and 2.16 kg.

[0145] 6. The curable composition of any preceding embodiment, wherein the polyolefin has a melting point (Tm) of 55°C, or 60°C, or 75°C, or 90°C, or 95°C, or 100°C to 105°C, or 110°C as measured using DSC.

[0146] 7. The curable composition of any preceding embodiment, wherein the polyolefin has a glass transition temperature, Tg, of -30°C or -35°C to -40°C, or -45°C, or -50, or -60°C as measured using DSC.

[0147] 8. The curable composition of any preceding embodiment, wherein the polyolefin has a flexural modulus (2% secant) of greater than, or equal to, 500 psi, or greater than, or equal to, 750 psi, or greater than, or equal to, 1000 psi to 2000 psi, or 3000 psi, or 3500 psi, or 4000 psi, or less than 6000 psi as measured according to ASTM D790.

[0148] 9. The curable composition of any preceding embodiment, wherein the polyolefin is an ethylene / α-olefin interpolymer.

[0149] 10. The curable composition of any preceding embodiment wherein the polyolefin is an ethylene / α-olefin copolymer.

[0150] 11. The curable composition of any preceding embodiment wherein the polyolefin is an ethylene / α-olefin random copolymer.

[0151] 12. The curable composition of any preceding embodiment wherein the polyolefin is an ethylene / 1-octene copolymer.

[0152] 13. The curable composition of any preceding embodiment wherein the fumed alumina is hydrophilic.

[0153] 14. The curable composition according to any of the preceding embodiments, wherein the fumed alumina has a specific surface area (BET) of greater than 50 m 2 / g to less than 200m 2 / g, or 55m 2 / g to 150m 2 / g, or 60m 2 / g to 140m 2 / g, or 65m 2 / g to 130m 2 / g.

[0154] 15. The curable composition of any one of the preceding embodiments, wherein the organic peroxide is selected from the group consisting of tert-butyl peroxy 2-ethylhexyl carbonate, dicumyl peroxide, dodecyl peroxide, benzoyl peroxide, tert-butyl perbenzoate, di(tert-butyl peroxide), cumene hydroperoxide, 2,5-dimethyl-2,5-di(tert-butyl-peroxy)hexyne-3, 2,-5-dimethyl-2,5-di(tert-butyl-peroxy)hexane, tert-butyl hydroperoxide, isopropyl percarbonate, α,α′-bis(tert-butylperoxy)diisopropylbenzene, 1,1-bis(tert-butylperoxy)-3,5,5-trimethylcyclohexane, 2,5-dimethyl-2,5-dihydroxyperoxide, tert-butylcumyl peroxide, α,α′-bis(tert-butylperoxy)-p-diisopropylbenzene, and combinations thereof.

[0155] 16. The curable composition of any preceding embodiment wherein the silane coupling agent is selected from the group consisting of 3-(trimethoxysilyl)propyl methacrylate, allyltrimethoxysilane, and combinations thereof.

[0156] 17. The curable composition of any preceding embodiment, wherein the crosslinking aid is selected from the group consisting of triallyl isocyanurate, triaryl cyanurate, triallyl phosphate, and combinations thereof.

[0157] 18. A sealant film comprising a crosslinked polymeric composition that is the reaction product of the curable composition of any one of the preceding embodiments.

[0158] 19. A sealant film comprising the curable composition of any of embodiments 1 to 17.

[0159] 20. A sealant film comprising the reaction product of the curable composition of any one of embodiments 1 to 17.

[0160] 21. The sealant film of any of Embodiments 18 to 20, wherein the volume resistivity of the sealant film is greater than 1.0E+15ohm.cm, or greater than 5.0E+15ohm.cm, or greater than or equal to 9.0E+15ohm.cm, or greater than or equal to 1.0E+16ohm.cm, or greater than or equal to 2.0E+16ohm.cm, or greater than or equal to 5.0E+16ohm.cm, or greater than or equal to 8.0E+16ohm.cm, or greater than or equal to 1.0E+17ohm.cm, or greater than or equal to 5.0E+17ohm.cm, or greater than or equal to 1.0E+18ohm.cm, or greater than or equal to 1.0E+19ohm.cm.

[0161] 22. The sealant film of any one of embodiments 18 to 21, wherein the volume resistivity of the sealant film is greater than 1.0E+15 ohm.cm to 1.0E+19 ohm.cm, or greater than 1.0E+15 ohm.cm to 1.0E+18 ohm.cm, or greater than 1.0E+15 ohm.cm to 5.0E+17 ohm.cm, or greater than 1.0E+15 ohm.cm to 1.0E+17 ohm.cm, or greater than 5.0E+15 ohm.cm to 1.0E+17, or greater than 9.0E+15 ohm.cm to 9.0E+16 ohm.cm.

[0162] 23. The sealant film of any one of embodiments 18 to 22, wherein the sealant film has a maximum torque (MH) greater than or equal to 2.0 dNm, or greater than or equal to 2.5 dNm, or greater than or equal to 3.0 dNm, or greater than or equal to 3.5 dNm, or greater than or equal to 3.6 dNm, or greater than or equal to 3.7 dNm.

[0163] 24. The sealant film of any of embodiments 18 to 23, wherein the sealant film has a t90 of less than 15 minutes, or less than 13 minutes, or less than 11 minutes, or less than 10.9 minutes, or less than or equal to 10.8 minutes, or less than or equal to 10.7 minutes.

[0164] 25. The sealant film of any of embodiments 18 to 24, wherein the sealant film has an initial glass adhesion of greater than 100 N / cm to 200 N / cm, or greater than 120 N / cm to 180 N / cm, or greater than 130 N / cm to 170 N / cm, or greater than 130 N / cm to 150 N / cm, or greater than 100 N / cm, or greater than 110 N / cm, or greater than 120 N / cm, or greater than 130 N / cm, or greater than 140 N / cm, or greater than 145 N / cm, or greater than or equal to 146 N / cm, or greater than or equal to 149 N / cm, or greater than or equal to 150 N / cm.

[0165] 26. The sealant film of any of embodiments 18 to 25, wherein the sealant film has an average transmittance greater than or equal to 88%, or greater than or equal to 88.5%, or greater than or equal to 89%, or greater than or equal to 89.5%, or greater than or equal to 90%.

[0166] 27. A PV module comprising a solar cell and the sealant film of any of embodiments 18 to 26.

[0167] 28. A PV module comprising solar cells and at least one layer, the layer being the sealant film of any of embodiments 18 to 26.

[0168] Examples

[0169] Material

[0170] The materials used in the following examples are described below.

[0171] "POE 1": Ethylene / 1-octene copolymer, can be used as ENGAGE TM 8411 was purchased from The Dow Chemical Company and had: a density of 0.880 g / cc (ASTM D792); a melt index of 18.0 g / 10 min (ASTM D1238 at 190°C / 2.16 kg); a Tm of 76°C; and a 2% secant = 20.5 MPa. The volume resistivity of POE 1 used herein (and available from The Dow Chemical Company upon request) was 1.0E+15 ohm.cm according to the methods disclosed herein.

[0172] "POE A": ethylene / 1-octene copolymer, available from The Dow Chemical Company, and having: a density of 0.880 g / cc (ASTM D792) and a melt index of 18.0 g / 10 min (ASTM D1238, at 190°C / 2.16 kg); a Tm of 76°C; and a 2% secant = 20.5 MPa, and a volume resistivity of 4.0E+16 ohm.cm according to the method disclosed herein.

[0173] “Peroxide”: tert-butylperoxy 2-ethylhexyl carbonate (TBEC), which is commercially available from J&K Scientific Ltd.

[0174] “Auxiliary agent”: triallyl isocyanurate (TAIC), which can be purchased from Fangruida Chemicals Co., Ltd.

[0175] "Alumina 1": pyrogenic aluminum oxide, which can be used as Alu 130 was purchased from Evonik Industries.

[0176] "Alumina 2": pyrogenic aluminum oxide, which can be used as Alu 65 was purchased from Evonik Industries.

[0177] "Silicon dioxide": fumed silica, which can be used as R812S was purchased from Evonik Industries.

[0178] “UV Stabilizer”: Bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, available from TCI as T770.

[0179] Silane coupling agent ("Silane"): 3-(trimethoxysilyl)propyl methacrylate, which is commercially available as VMMS from Dow Corning.

[0180] Sample preparation

[0181] Each of the comparative samples (CS1 to CS6) and inventive examples (IE1 to IE4) was prepared as described below and according to the formulation of Table 1.

[0182] Ethylene / 1-octene copolymer pellets were fed into a Brabender mixer at a temperature of 130° C. and a rotor speed of 10 rpm. Fumed alumina or fumed silica (depending on the formulation of Table 1) was then added. Final mixing was performed at 130° C. and a rotor speed of 80 rpm for 5 minutes. The resulting compound was collected and cut into small pieces.

[0183] Small pieces of ethylene / 1-octene copolymer and alumina / silica (or only ethylene / 1-octene copolymer if no alumina or silica is added) are fed into the hopper of a Brabender single extruder. The small pieces are extruded into a melt column at 110°C and a screw speed of 25 rpm. The melt strand is fed to a Brabender pelletizer to prepare pellets.

[0184] Silane coupling agent, organic peroxide, auxiliary agent and any additional additives such as UV stabilizer and / or antioxidant are weighed according to Table 1 below and mixed in a sealable plastic bottle. Pellets are weighed according to Table 1 and added to the plastic bottle. To ensure uniform distribution and complete immersion, the plastic bottle is first tumbled for 1 minute and then placed on a running roller and further homogenized in an oven at 40°C for 15-20 hours before use.

[0185] Membrane preparation

[0186] After soaking, the pellets were fed into a Brabender single screw mixer at a rotor speed of 30 rpm at 105° C. Films with a thickness of approximately 0.5 mm were prepared and stored in sealed aluminum foil bags for testing.

[0187] Compression molding

[0188] The cast film was compression molded into a 0.5 mm film. The sample was placed in the mold, preheated to 120°C for 5 minutes, and then degassed by 8 pressure loading / releasing cycles. The degassed sample was then pressurized at 150°C for 15 minutes and cooled to room temperature. The compression molded sheets were used for volume resistivity and transmittance testing.

[0189] laminated

[0190] The 4" x 6" glass plate was cleaned with water and dried before use. The backsheet was cut into four 6-inch squares. The film sample was cut into sheets to fit the size of the glass and backsheet. The backsheet, film sample, and glass were laminated together to form a backsheet / film sample / glass structure, and then laminated on a PENERGY L036 laminator at 150°C for 20 minutes (4 minutes vacuum and 16 minutes press). The laminated samples were used for glass adhesion testing.

[0191] Table 1.

[0192]

[0193] Comparative Example 1 (CE1) is a sealant film based on an ethylene / α-olefin copolymer having a volume resistivity of 1.0E+15 ohm.cm. As seen in Comparative Example 2 (CE2), the addition of fumed silica with the same level of additives did not provide significant VR improvements. Similarly, as seen in Comparative Examples 3-6 (CE3 to CE6), the addition of fumed alumina (with the same level of additives) based on an ethylene / α-olefin copolymer having a higher VR (volume resistivity of 4.0E+16 ohm.cm) did not provide significant VR improvements.

[0194] In contrast, Inventive Examples 1-4 (IE1 to IE4) surprisingly show that the addition of fumed alumina with the same level of additives provides a significant VR improvement while maintaining other key properties, such as good cure performance and good adhesion performance. In fact, IE1 to IE4 show more than 10 times and even more than 100 times (2 orders of magnitude) of VR improvement while also maintaining similar or comparable cure and adhesion performance to CE1. This huge improvement in VR for a formulation based on an ethylene / α-olefin copolymer with a low VR without affecting cure and adhesion is surprising and unexpected.

Claims

1. A curable composition for a sealant film, the curable composition comprising: (A) 80 wt% to 99 wt% of a polyolefin based on the total weight of the curable composition; (B) 0.1 wt% to 2 wt% of a fumed alumina; (C) an organic peroxide; (D) a silane coupling agent; (E) a crosslinking aid; and, optionally, (F) an additive component comprising a UV stabilizer, wherein the polyolefin is an ethylene / α-olefin copolymer and has a volume resistivity of less than 4.0E+15 ohm·cm as measured according to ASTM D257, and the fumed alumina has a BET specific surface area of ​​greater than 50 m 2 / g and less than 200 m 2 / g.

2. A curable composition for a sealant film, wherein the curable composition comprises: (A) 80 wt % to 99 wt % of a polyolefin, based on the total weight of the curable composition; (B) 0.1 wt % to 2 wt % of fumed alumina, based on the total weight of the curable composition; (C) 0.1 wt % to 5 wt % of an organic peroxide, based on the total weight of the curable composition; (D) 0.01 wt % to 2 wt % of a silane coupling agent, based on the total weight of the curable composition; (E) 0.01 wt % to 5 wt % of a crosslinking aid, based on the total weight of the curable composition; and (F) 0 wt % to 3 wt % of a UV stabilizer, based on the total weight of the curable composition; wherein the polyolefin is an ethylene / α-olefin copolymer and has a volume resistivity of less than 4.0E+15 ohm·cm measured according to ASTM D257, and the fumed alumina has a BET specific surface area of ​​greater than 50 m 2 / g and less than 200 m 2 / g.

3. The curable composition according to claim 1 or 2, wherein the volume resistivity of the polyolefin measured according to ASTM D257 is greater than 1.0E+12 ohm·cm and less than 4.0E+15 ohm·cm.

4. The curable composition of claim 1 or 2, wherein the polyolefin has a density of 0.860 g / cc to 0.890 g / cc.

5. The curable composition of claim 1 or 2, wherein the polyolefin has a melt index of 1 g / 10 min to 100 g / 10 min, wherein the melt index is measured according to ASTM D1238, Condition 190°C / 2.16 kg weight.

6. The curable composition according to claim 1 or 2, wherein the α-olefin is selected from propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-dodecene and mixtures thereof.

7. The curable composition of claim 1 or 2, wherein the polyolefin is an ethylene / octene copolymer.

8. The curable composition according to claim 1 or 2, wherein the fumed alumina has a BET specific surface area of ​​55 m 2 / g to 150 m 2 / g.

9. A sealant film comprising a cross-linked polymeric composition which is a reaction product of the curable composition according to any one of claims 1 to 8. 10 . The sealant film of claim 9 , wherein the sealant film has a volume resistivity measured according to ASTM D257 of greater than 9.0E+15 ohm·cm and less than or equal to 9.0E+16 ohm·cm. 11 . The sealant film according to claim 9 or 10 , wherein a maximum torque MH of the sealant film is greater than or equal to 2.0 dN·m.

12. The sealant film of claim 9 or 10, wherein the sealant film has a t90 of less than 13 minutes.

13. The sealant film of claim 9 or 10, wherein the sealant film has an initial glass adhesion of greater than 100 N / cm.

14. The sealant film of claim 9 or 10, wherein the sealant film has an average transmittance greater than or equal to 88%.

15. A PV module comprising solar cells and the sealant film according to any one of claims 9 to 14.

Citation Information

Patent Citations

  • Catalyst composition comprising shuttling agent for ethylene multi-block copolymer formation

    US7858706B2

  • Catalyst composition comprising shuttling agent for ethylene multi-block copolymer formation

    US8198374B2

  • Functionalized ethylene / α-olefin interpolymer compositions

    US8318864B2

  • Functionalized ethylene / alpha-olefin interpolymer compositions

    US8609779B2

  • Catalyst composition comprising shuttling agent for ethylene multi-block copolymer formation

    US8710143B2